Listening Skills for Learning German Using Blended Learning Models - Risnovita Sari; Rina Evianty; Muhammad Amran (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Listening skills are one of the skills in learning German. Listening skills are also a very important skill in the learning process to improve German language skills. The ability to actively listen is defined as the process of actively understanding to get information, and the attitude of the speaker whose purpose is to understand the conversation objectively. In the current era of globalization many online learning methods have been applied, one of which is the Blended Learning model. Blended Learning is a combination of face-to-face learning and online learning.